TEACHING WRITING OF PROCEDURE TEXT THROUGH DEMONSTRATION TECHNIQUE - Miliana, Arman Putra; Regina, Regina; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research investigated Teaching Writing Procedure Text through Demonstration Technique and finding the effect size of the treatment through Demonstration to the tenth grade students of SMA IBM Pontianak. The form of this research was a pre-experimental study with one group pre-test and post-test design. The population was the tenth grade students of SMA IBM Pontianak, while the sample was class X which consists of 20 students. The technique used in data collection was measurement technique and the tool for the data collection was a test in form of written test. The research finding showed that the mean score of pre-test was 34.70 while the mean score of post-test was 62.5. The result of t-test was 27.8. It was higher than t-critical at a0,05 (7.35>1.729). As a result, the alternative hypothesis (Ha) was accepted. The calculation of the effect size of the treatments was 1.61 which was categorized as high since 0.2 Â ES (1.61>0.8).It can be concluded that there was a moderate significant effect from Teaching Writing Procedure Text through Demonstration Technique to the tenth grade students of SMA IBM Pontianak.Â Keywords: Teaching Writing, Procedure Text, Demonstration Technique.